TUBEROUS SKLEROSIS PADA ANAK - Ayamiseba, Sandra; Suling, Pieter L. (JURNAL BIOMEDIK : JBM, 2015)
Abstract: Tuberous sclerosis (TS) is an autosomal dominant disease associated with mutation of one of two different genes, TSC1 or TSC2. The typical clinical picture of TS cases is skin lesions, mental retardation, and epilepsy. According to the consensus of TS alliance, the US National Tuberous Sclerosis Association, in July 1998, the diagnostic criteria of TS are based on major and minor symptoms: two major symptoms, or one major and two minor symptoms. The management of the skin disorders such as angiofibroma with a cosmetic purpose can be done by using electrocauterization, dermabrasion, and excision. The prognosis depends on the systemic involvement. We reported a case of a male, aged 7 years, with 2 major symptoms of TS: facial angiofibroma that spreaded to his neck and back, and hypomelanotic macula on his back. The histopathological examination showed subepithelial keratosis associated with fibrocollagen tissue and teleangiectasis in the stroma, atrophy of sebacceous glands, without any malignancy. Conclusion: In this case, the diagnosis of tuberous sclerosis was based on anamnesis, clinical picture (two major symptoms), and histopathological examination. Electrocauterization could not be performed because the patient was incooperative. The prognosis was quo ad vitam, quo ad functionam, quo ad sanationam: dubia.Keywords: tuberous sclerosis, multiple hyperpigmented noduleAbstrak: Tuberous sklerosis (TS) merupakan suatu penyakit autosomal dominan yang dihubungkan dengan mutasi satu dari dua gen yang berbeda, yaitu TSC1 atau TSC2. Gambaran klinis yang khas pada kasus ini ialah lesi kulit, retardasi mental, dan epilepsi. Berdasarkan konsensus aliansi US National Tuberous Sclerosis Association pada Juli 1998 dirumuskan kriteria diagnostik berdasarkan adanya gejala mayor dan minor, yaitu dua gejala mayor; atau satu gejala mayor dan dua gejala minor. Prinsip pengobatan untuk kelainan kulit berupa angiofibroma dengan tujuan kosmetik yaitu dengan elektrokauter, dermabrasi, dan eksisi. Prognosis tergantung pada keterlibatan sistemik. Pada kasus ini ditemukan 2 gejala mayor yaitu angiofibroma pada wajah yang menyebar ke leher dan punggung serta makula hipomelanotik pada punggung. Pemeriksaan histopatologik jaringan menunjukkan hiperkeratosis subepitelial di lapisan epidermis. Tampak stroma jaringan ikat fibrokolagen dengan pelebaran pembuluh darah kapiler, kelenjar sebaseus atrofi, dan tidak didapatkan tanda-tanda keganasan. Simpulan: Pada kasus ini, diagnosis TS ditegakkan berdasarkan anamnesis, gambaran klinis (2 gejala mayor), dan pemeriksaan histopatologik. Penatalaksanaan dengan elektrokauter tidak dapat dilakukan karena pasien tidak kooperatif. Prognosis tergantung gejala klinis, quo ad vitam, quo ad functionam, quo ad sanationam: dubia.Kata kunci: tuberous sklerosis, nodul hiperpigmentasi multipel